A molecular zipping/unzipping nano-vehicles sensitive to tumor extracellular pH. (July 2014) - Lee, Jung Ok; Lee, Min Ji; Kim, Dongin; Lee, Eun Seong
A new class of pH- responsive multivalent host –guest interactions to manipulate polypeptide-based nano-vehicles was developed. Poly(l -lysine) (poly(Lys)) grafted with β-cyclodextrin and 2, 3-dimethylmaleic acid was coupled with oleic acid. This new polymer was utilized to fabricate pH-responsive nano-vehicles for antitumor drug doxorubicin delivery. The host–guest (zipping) interaction between β-cyclodextrin and 2, 3-dimethylmaleic acid moieties and the hydrophobic interaction between the oleic acid molecules contributed to form self-assembled nano-vehicles. 2, 3-Dimethylmaleic acid moieties were highly degradable at a slightly acidic pH ( pH 6.8). These nano-vehicles increased the release of the encapsulated doxorubicin content (by the unzipping interaction between β-cyclodextrin and degraded 2, 3-dimethylmaleic acid moieties) when the pH of the solution decreased to 6.8. This event caused a significant increase in the efficiency of cellular doxorubicin uptake and in vitro tumor inhibition.